(untitled) (Psico, 2006)
Anamélia Lins e Silva Franco Universidade católica de Salvador (UCSAL) Vânia Sampaio Alves ISC/UFBA A relação médico-paciente tem sido reconhecida como problema de saúde pública. Estudos têm caracterizado esta relação a partir de padrões ideais identificados a partir da aplicação de escalas e de registros a posteriori. O presente estudo pretendeu avançar nas estratégias metodológicas de apreensão e interpretação da relação médico-paciente no contexto do Programa Saúde da Família (PSF). Problematizando a abordagem da dimensão psicossocial do processo saúde-doença pelo médico e o desenvolvimento da autonomia dos pacientes, analisaram-se 408 consultas de 20 médicos. As consultas foram observadas sob orientação de um instrumento observacional e registradas em áudio. Os dados do instrumento observacional, aprofundados pela análise de conteúdo das consultas de 10 médicos, demonstram que a dimensão psicossocial não foi abordada na maioria destas consultas. Observou-se predomínio do padrão biomédico de relação médicopaciente, com o profissional assumido uma postura não-dialógica, circunstância desfavorecedora do desenvolvimento da autonomia dos pacientes. Palavras-chave: Relação médico-paciente; psicossocial; autonomia do paciente. ABSTRACT The psychosocial dimension and the patient’s autonomy: challenges to the doctor-patient relationship in the Family Health Program The doctor-patient relationship has been recognized as a public health problem. Studies have described this relationship based on ideal standards from the application of scales and records. This study aimed at advancing in the methodological strategies of collection and interpretation of the doctor-patient relationship in the context of the Family Health Program (PSF). The psychosocial dimension in the the health-disease process and the development of patient autonomy were discussed and analysed in 408 consultations of 20 doctors. An observational instrument was used in the consultation, which were which were recorded in cassettes. The data collect, together with the content analyses of consultations of 10 doctors, showed that the psychosocial dimension was not dealt with in the majority of these consultations. The most common relationship was of a biomedical pattern where the physician did not promote a dialogue and therefore did not favor patient autonomy. Key words: Doctor-patient relationship; psychosocial; patient autonomy.